Pemanfaatan Bentos sebagai Bioindikator Kesehatan Lingkungan pada Kolam Budidaya di Pokdakan Teratai Putih Emas - Siska Almaniar; Tiara Santeri; Junainah Junainah; Desliana Opie Harliani; Leni Maryani; Roni Abriansyah; Galih Rakha Dewi (Universitas Muhammadiyah Palembang, 2026)
Intensive aquaculture activities are prone to environmental quality degradation due to the accumulation of feed residues and organic matter at the pond bottom. One simple approach to monitor aquatic environmental health is through the observation of benthos as a bioindicator. This community service activity aimed to improve the knowledge and awareness of members of Pokdakan Teratai Putih Emas in Kelurahan Empat Belas Ulu, Palembang City, regarding the utilization of benthos as an environmental health indicator for aquaculture ponds. The methods used included initial observation, participatory material delivery, interactive discussion, and participant comprehension evaluation. The activity was attended by 15 Pokdakan members who previously assessed water quality only based on water color and fish condition. Following the activity, participants were able to identify common benthos types (worms, insect larvae, and mollusks) and understand their relationship with bottom water conditions. Evaluation results showed an improvement in participant comprehension of more than 70% based on discussion and question-and-answer sessions. This activity had a positive impact on community awareness in managing aquaculture pond environmental quality sustainably to support fishery productivity.